Guía de prácticas de higiene en frutas y hortalizas para centros de acopio, que garanticen la inocuidad de sus productos - Saeteros Pérez, Evelin Estrella (2020)
ABSTRACT: This thesis's main objective is to train the people who work in the fruit and vegetable collection centers so that they improve the quality of their products and obtain better benefits. Fruits and vegetables are the primary sources of food for the entire human population; for this reason, these products must reach the consumer's table in optimal conditions. This thesis shows seven techniques or methods of cleaning and disinfection of fruits and vegetables. Vegetables guarantee better quality and physical and microbial safety for consumption; these techniques are easy to use. Similarly, it investigated the physical, chemical, and microbiological risks to which fruit and vegetables are exposed. A comparison matrix of the different methods was made. Finally, the guide to correct hygiene practices in fruits and vegetables was also carried out. It is specified that the final quality of any food product does not only depend on the cleaning and disinfection that can be given. Since quality is a set of everything, from the field applying GAP and later with GMP, following these standards properly, the risks of contamination are also significantly reduced.